Transcriptome analysis of ischemic stroke recovery induced by neural stem cell preconditioned with baicalein-enriched fraction of oroxylum indicum - Satar, Asmaa’ Mohd (2024)
Ischemic stroke is one of the leading causes of death and a major contributor to adult disability worldwide. Transplantation of regenerative stem cells preconditioned with natural products was applied to restore the damaged neural circuity after an attack of ischemic stroke. However, the key regulators and pathways underlying such recovery are still mainly unknown. In this study, neural stem cells (NSCs) preconditioned with baicalein enriched fraction (BEF), a neuroprotective active compound extracted from a local medicinal plant known as Oroxylum indicum (O. indicum), was transplanted into an ischemic stroke rat model and a transcriptome analysis was applied to profile the brain total ribonucleic acid (RNA) expression to identify the key genes and pathways underlying the ischemic stroke recovery induced by the preconditioned NSC transplantation. A total of 15 Sprague-Dawley (SD) rats were injected with endothelin-1 (ET-1) to occlude the middle cerebral artery (MCA) blood vessel inside the brain, mimicking the ischemic stroke disease in human. The ET-1 induced ischemic stroke rat models were randomly assigned into 3 subgroups, namely Group 1: Non-treated (control group, n = 5), Group 2: Treated with non-preconditioned NSCs (n = 5) and Group 3: Treated with BEF-preconditioned NSCs (n = 5). The animal neurological behaviours were monitored and scored based on modified neurological severity score (mNSS) test, cylinder test and grid-walking test for 14 days (p-value < 0.05). After 14 days, all the rats were sacrificed by intraperitoneal injection of ketamine (200 mg/kg) and Xylazine (20 mg/kg). The brain issues were harvested and snap-frozen using liquid nitrogen to homogenize the brain tissue for RNA extraction. The extracted RNA was analysed using microarray assay to reveal differentially expressed genes (DEGs), gene ontology (GO) and biological pathways related to neurological behavior improvement of the rats. The results revealed that the experimental rats treated with NSCs preconditioned with BEF at 3.125 µg/mL for 48 hours improved neurological behavioral function as fast as just 24 hours after the treatment (p-value < 0.05), compared to rats treated with non-preconditioned NSCs and non-treated group. Furthermore, based on microarray result showed the expression of GABRA6, NGF, JAKMIP1, DRD3, STAT6, NF-κβ, SLC6A3 and IL-1RN were significantly identified based on the top 10 of DEGs (p-value < 0.05), Gene Ontology (p-value < 0.05) and biological pathways using KEGG pathways analysis (p-value < 0.05). The key regulated pathways such as cAMP signaling pathway, Toll-like receptor signaling pathway, B-cell receptor signaling pathway and Fc gamma R-mediated phagocytosis were associated with the improvement of neurological behavior in the ischemic stroke rat model. In brief, this study provides new knowledge regarding the mechanism of BEF-preconditioned NSCs therapy to treat ischemic stroke based on the significant main expression of genes using microarray analysis.